Simulating humans : computer graphics animation and control - Badler, Norman I. (Oxford University Press, 1993)
Though actively pursued by several research groups, the problem of providing a synthetic or surrogate human for an engineer or designer already used to Computer Aided Design techniques has been most comprehensively solved by Norman Badler's computer graphics laboratory at the University of Pennsylvania - one of the world leaders in the field of simulated human figures in computer graphics. For human factors engineers, this book provides current knowledge of how a computer graphics surrogate human can augment their analyses of designed environments; for design engineers it presents the cutting edge in human figure modelling and hence human-centred design and for the computer graphics community it presents a major research effort in the interactive control of articulated human figures. This book constitutes the state of the art in simulating human figures, discusses the many areas of application and predicts the future in this exciting, fast moving field.